COVID-19-Associated Cerebral White Matter Injury in a Newborn Infant With Afebrile Seizure. Issue 7 (July 2021) - Yildiz, Harun; Yarci, Erbu; Bozdemir, Sefika Elmas; Ozdinc Kizilay, Nesrin; Mengi, Senay; Beskardesler, Naciye; Korukluoglu, Gulay; Mueller, Andreas; Bagci, Soyhan
Abstract : Coronavirus disease 2019 (COVID-19) symptoms in newborn infants are incompletely described. We present the first case of neuroradiologic abnormality associated with COVID-19 in a newborn infant with afebrile seizure. This case underlines the possible neurologic involvement of severe acute respiratory syndrome coronavirus 2 in this age group. Abstract : Supplemental Digital Content is available in the text.